THE BRIDGE STRUCTURE TESTS UNDER SLOW MOVING LOAD - Sukhorukov, B. D. (Science and Transport Progress, 2010)
Peculiarities and advantages of bridge structure tests under slow moving load are pointed out. The calculation algorithms for finding in-situ influence line ordinates based on the results of the tests are proposed.